After the Black Death economy, society, and the law in fourteenth-century England - Bailey, Mark 1960- (Oxford scholarship online, 2021)
The Black Death of 1348-9 was the most catastrophic event and worst pandemic in recorded history. 'After the Black Death' offers a major reinterpretation of its immediate impact and longer-term consequences in England